2019
DOI: 10.1590/01047760201925022617
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Motion and Postural Analysis of Machine Operators in Mechanized Wood Harvesting Operations

Abstract: LOPES, E. S.; SOUZA, A. P.; OLIVEIRA, F. M.; RODRIGUES, C. K. Repetitive motion and postural analysis of machine operators in mechanized wood harvesting operations. CERNE, v. 25, n. 2, p.214-220, 2019. HIGHLIGHTSFeller buncher operators have adopted only one posture during the entire working day.Difficult visibility of the operation contributed to the adoption of improper posture at work. Repetitive motions may contribute to the RSI/MSDs.Ergonomic measures should be adopted to improve operators' comfort and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Some studies presented the results following assessment by two or three methods, but did not explicitly provide the agreement rates between the methods in the original articles. The agreement rates by Cremasco et al [ 38 ], Kulkarni and Devalkar [ 42 ], Gallo and Mazzetto [ 47 ], Garcia et al [ 48 ], Noh and Roh [ 49 ], Sahu et al [ 52 ], and Paini et al [ 67 ] were calculated using the assessment results presented in the original studies by the author of this study, and those by Kee et al [ 25 ] were obtained using the experimental data. The agreements among the three methods varied depending on the studies ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies presented the results following assessment by two or three methods, but did not explicitly provide the agreement rates between the methods in the original articles. The agreement rates by Cremasco et al [ 38 ], Kulkarni and Devalkar [ 42 ], Gallo and Mazzetto [ 47 ], Garcia et al [ 48 ], Noh and Roh [ 49 ], Sahu et al [ 52 ], and Paini et al [ 67 ] were calculated using the assessment results presented in the original studies by the author of this study, and those by Kee et al [ 25 ] were obtained using the experimental data. The agreements among the three methods varied depending on the studies ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review results should be interpreted with caution, because (1) some studies had extremely small sample sizes or number of raters (sample sizes for Pal and Dhara [ 36 ], Cremasco et al [ 38 ], Noh and Roh [ 49 ], Boulila et al [ 60 ], Dev et al [ 61 ], Paini et al [ 67 ], and Kamath et al [ 71 ] in Table 2 were <10), (2) the agreements and correlations showed large standard deviations ( Table 3 and Table 4 ), and (3) this study is mainly based on the literature by various researchers with different experiences and fields of knowledge. These may generate bias in their results.…”
Section: Discussionmentioning
confidence: 99%
“…The workers were mostly exposed to machine-assisted tasks and roles, thus corroborating that during working hours the worker performs static and repetitive machinery control operations 19 , 20 using specific body segments where there is a risk of vibration and litle physical activity that allows the recovery of musculoskeletal tissues. 21 , 22 …”
Section: Discussionmentioning
confidence: 54%
“…The analysis of human posture is essential to identify musculoskeletal disorders inherent to the workplace; however, postural data and joint angles are necessary for a correct ergonomic evaluation [21]. [22] showed that operations related to wood processing usually affect the spine and neck area, which generates a significant level of risk. However, there are tasks that require repetitive movements which can generate a high level of risk and therefore an injury to workers.…”
Section: Discussionmentioning
confidence: 99%